Rosai and Ackerman's surgical pathology - Rosai, Juan, 1940-; Ackerman, Lauren V., 1905-1993; Rosai, Juan, 1940- (Edinburgh ; New York : Mosby, an imprint of Elsevier Incorporated, 2011)
The seven years that have elapsed between the current and the previous editions of this book have seen momentous changes taking place in the practice of surgical pathology. Immunohistochemistry has continued its notable expansion and has become an indispensable adjunct for the practice of the specialty. It has truly transformed the practice of surgical pathology in a fashion that no other technique has done before or after. Newcomers to the specialty take it for granted when ordering their panels, without pausing to think that only forty years ago none of this was available to the brave pathologists who based all of their diagnoses and other considerations on patterns of growth and cellular features seen in hematoxylin-stained slides, with the occasional modest help provided by one or another 'special stain'. We are now in the midst of another transformation, resulting from the application to surgical pathology specimens of the enormous amount of new knowledge derived from the molecular genetic revolution. The potential and - in some instances - the already tangible benefits of this technology are too obvious to be emphasized. It may instead be instructive to reflect on the effect that this barrage of new information is having on the approach to surgical pathology by the new generation of practitioners, and the danger that the tradition of meticulous gross and microscopic examination upon which surgical pathology has been built may be gradually eroding. Some of this may be inevitable and is perhaps not altogether undesirable, yet the amount of information that this time honored examination can still provide is so rich and dependable that one recoils at the thought of it being belittled or altogether ignored. With that caveat in mind, this edition dutifully incorporates the many promising results reached with the new technologies (emphasizing those in which a clinical validation has occurred), but always matching them against the results and conclusions derived from the morphology-based approach that has served pathologists so well for so long. This difficult integration task has been carried out in most chapters by Dr. John KC Chan, a brilliant representative of that emerging and still sparse cadre of surgical pathologists who combine a superb knowledge of conventional pathology with an understanding of the principles, possible applications and potential pitfalls of molecular genetic techniques. Another important change that has taken place during this period concerns the increasing demands for standardization, compliance with regulatory controls and legal accountability, which have prompted various pathology organizations to produce sets of guidelines to help us navigate through an increasingly complicated terrain. Yet another significant development concerns the pervasive influence acquired by electronic information systems in practically all activities that take place in the surgical pathology laboratory, rendering some degree of computer literacy indispensable to those wishing to practice the specialty. It has not been easy to accommodate this rapidly changing and continuously expanding universe within the confines of the covers of this book
Volume 1 -- Introduction -- Gross techniques in surgical pathology -- Special techniques in surgical pathology -- Skin -- dermatoses -- Skin -- tumors and tumorlike conditions -- Oral cavity and oropharynx -- Mandible and maxilla -- Respiratory tract -- nasal cavity, paranasal sinuses, and nasopharynx -- Respiratory tract -- larynx and trachea -- Respiratory tract -- lung and pleura -- Mediastinum -- Thyroid gland (with giovanni tallini) -- Parathyroid glands -- Gastrointestinal tract -- esophagus -- Gastrointestinal tract -- stomach -- Gastrointestinal tract -- small bowel -- Gastrointestinal tract -- appendix -- Gastrointestinal tract -- large bowel -- Gastrointestional tract -- anus -- Major and minor salivary glands -- Liver -- non-neoplastic diseases -- Liver -- tumors and tumorlike conditions -- Gallbladder and extrahepatic bile ducts -- Pancreas and ampullary region -- Adrenal gland and other paraganglia -- Urinary tract -- kidney, renal pelvis, and ureter: non-neoplastic diseases -- Urinary tract -- kidney, renal pelvis, and ureter: pediatric tumors and tumorlike conditions/adult tumors and tumorlike conditions -- Urinary tract -- bladder -- Male reproductive system -- prostate and seminal vesicles -- Male reproductive system -- testis -- Male reproductive system -- testicular adnexa -- Male reproductive system -- penis and scrotum Volume 2 -- Female reproductive system -- vulva -- Female reproductive system -- vagina -- Female reproductive system -- uterus: cervix -- Female reproductive system -- uterus: corpus -- Female reproductive system -- fallopian tube -- Female reproductive system -- ovary -- Female reproductive system -- placenta -- Breast -- Lymph nodes -- Spleen -- Bone marrow -- Bone and joints -- Soft tissues -- Peritoneum, retroperitoneum, and related structures -- Cardiovascular system -- heart -- Cardiovascular system -- arteries -- Cardiovascular system -- veins -- Cardiovascular system -- lymph vessels -- Central nervous system -- Pituitary gland -- Eye and ocular adnexa -- Ear
Previous edition: published as Ackerman's surgical pathology. 1996
"Expert consult"--Cover
Includes bibliographical references and index
Keywords: Pathology, Surgical; Pathology, Surgical